2016
DOI: 10.1016/j.cortex.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Slow wave sleep and accelerated forgetting

Abstract: We investigated whether the benefit of slow wave sleep (SWS) for memory consolidation typically observed in healthy individuals is disrupted in people with accelerated long-term forgetting (ALF) due to epilepsy. SWS is thought to play an active role in declarative memory in healthy individuals and, furthermore, electrographic epileptiform activity is often more prevalent during SWS than during wakefulness or other sleep stages. We studied the relationship between SWS and the benefit of sleep for memory retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 99 publications
1
24
0
Order By: Relevance
“…On the other hand, the negative correlation we detected between % SWS and overnight retention of the RCFT is similar to results by Atherton and colleagues [57] in patients with transient epileptic amnesia. They found %SWS to be negatively correlated with overnight sleep benefit for word pair retention in the patients (but not in healthy controls).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the negative correlation we detected between % SWS and overnight retention of the RCFT is similar to results by Atherton and colleagues [57] in patients with transient epileptic amnesia. They found %SWS to be negatively correlated with overnight sleep benefit for word pair retention in the patients (but not in healthy controls).…”
Section: Discussionsupporting
confidence: 92%
“…Whilst group differences in the magnitude of association between sleep variables and behavioural measures should be interpreted cautiously (e.g., as a consequence of small sample sizes), the view that sleep may support the consolidation of vocabulary learning to a lesser extent in children with dyslexia is consistent with previous findings from other populations with learning difficulties (e.g., Adi‐Japha, Strulovich‐Schwartz, & Julius, ; Henderson et al., ). For example, a recent study with adults who have accelerated forgetting due to epilepsy demonstrated that similar patterns of consolidation on behavioural measures can mask differences in neural processes (Atherton et al., ). Both patient and control groups showed similar patterns of recall across all testing sessions, but whereas consolidation was positively related to slow wave sleep duration in the controls, there was a negative relationship for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Retroactive interference accounts of forgetting argue that learning and mental activity that occurs after encoding contributes to memory loss (Wixted 2004). Consistent with this view, rates of forgetting are typically reduced across sleep relative to wakefulness (Jenkins and Dallenbach 1924;Newman 1938; Barrett and Ekstrand 1972;Plihal and Born 1997;Gais et al 2006;Tucker et al 2006;Tamminen et al 2010;Payne et al 2012;Atherton et al 2016;Cairney et al 2018a,b), as sleep shelters new memories from competing information.…”
mentioning
confidence: 96%